2020
DOI: 10.1161/jaha.119.014066
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Intracoronary Alteplase on Microvascular Function in Acute Myocardial Infarction

Abstract: Background--Impaired microcirculatory reperfusion worsens prognosis following acute ST-segment-elevation myocardial infarction. In the T-TIME (A Trial of Low-Dose Adjunctive Alteplase During Primary PCI) trial, microvascular obstruction on cardiovascular magnetic resonance imaging did not differ with adjunctive, low-dose, intracoronary alteplase (10 or 20 mg) versus placebo during primary percutaneous coronary intervention. We evaluated the effects of intracoronary alteplase, during primary percutaneous corona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 36 publications
1
13
0
2
Order By: Relevance
“…As a confirmation of this hypothesis, in our cohort, the median value of RRR—a dedicated index to express the vasodilatory capacity of the coronary microcirculation—was 1.7. This value is suggestive of a depressed coronary microvascular vasodilatory capacity in this cohort of patients with STEMI, a finding consistent with previous reports ( 12 , 13 ). This depressed vasodilatory capacity can explain why, particularly in patients with STEMI, a non-hyperaemic index such as NH IMR angio retains some diagnostic accuracy in identifying microvascular injury ( 14 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…As a confirmation of this hypothesis, in our cohort, the median value of RRR—a dedicated index to express the vasodilatory capacity of the coronary microcirculation—was 1.7. This value is suggestive of a depressed coronary microvascular vasodilatory capacity in this cohort of patients with STEMI, a finding consistent with previous reports ( 12 , 13 ). This depressed vasodilatory capacity can explain why, particularly in patients with STEMI, a non-hyperaemic index such as NH IMR angio retains some diagnostic accuracy in identifying microvascular injury ( 14 ).…”
Section: Discussionsupporting
confidence: 92%
“…It is reported that in most patients with STEMI the vasodilatory capacity of the microvascular coronary bed is blunted and consequently the response of coronary microcirculation to adenosine is often minimal or incomplete. ( 12 , 13 ). In this regard, we have recently described the non-hyperaemic version of IMR angio –NH IMR angio , and shown it retains its diagnostic reliability in most patients with STEMI ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…The PRISMA flowchart is shown in Figure 1. After screening 2490 records, we identified 15 articles to include in our meta‐analysis 26–41 . Results for IMR stratified by the presence of MVO were available in eight included studies 15,26,27,30,31,34,36,40,41 .…”
Section: Resultsmentioning
confidence: 99%
“…32], with the mean difference in IMR of15.1 [9.7−20.6] (2). The diagnostic utility of IMR with traditional cut-off value of 40 to assess MVO was modest (sensitivity 69% and specificity 65%) based on our SROC curve analysis.…”
mentioning
confidence: 80%
“…Indeed, GpIIb/IIIa was predominantly (72%) used as a bailout strategy after thrombus aspiration. Nonetheless this is unlikely to confound our endpoint as insights from the T-TIME randomised trial show that intracoronary thrombolysis had no effect on microvascular injury indices ( 30 ).…”
Section: Limitationsmentioning
confidence: 99%